2016
DOI: 10.3892/mmr.2016.4822
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic study of high-glucose effects on human skin fibroblast cells

Abstract: Abstract. Skin ulcers are a common complication of diabetes mellitus (DM). Fibroblasts are located within the dermis of skin tissue and can be damaged by diabetes. However, the underlying mechanism of how DM affects fibroblasts remains elusive. To understand the effects of DM on fibroblasts, the current study mimicked DM by high-glucose (HG) supplementation in the culture medium of human foreskin primary fibroblast cells, and the analysis of transcriptomic changes was conducted. RNA sequencing-based transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Initially, HG concentration was optimized for the relevant experimental conditions prior to testing gene expression. Previous research has identified that HG concentrations >35 mM significantly inhibit cell proliferation (11). In the present study, it was confirmed that 35 mM HG stress significantly reduced fibroblast proliferation, in comparison with LG fibroblasts (Fig.…”
Section: Hg Inhibits Cell Proliferation and Hedgehog Signaling In Skisupporting
confidence: 88%
See 2 more Smart Citations
“…Initially, HG concentration was optimized for the relevant experimental conditions prior to testing gene expression. Previous research has identified that HG concentrations >35 mM significantly inhibit cell proliferation (11). In the present study, it was confirmed that 35 mM HG stress significantly reduced fibroblast proliferation, in comparison with LG fibroblasts (Fig.…”
Section: Hg Inhibits Cell Proliferation and Hedgehog Signaling In Skisupporting
confidence: 88%
“…To understand the mechanism of diabetes, HG is typically used to mimic the disease. Previous studies have observed that HG mediated stress altered the expression of many genes including hedgehog signaling-related genes in human fibroblast primary cells (11). To analyze the effect of HG on hedgehog signaling, key genes associated the pathway were examined for HG-mediated changes in expression.…”
Section: Hg Inhibits Cell Proliferation and Hedgehog Signaling In Skimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NOD-like receptor signaling was altered upon HG stress in VECs. Decreased NOD-like signaling in human fibroblast cells with HG stress were also observed in a previous study (12). Furthermore, genetic variation of NOD1 and NOD2 has been associated with type II DM (23), suggesting the importance of NOD-like signaling in DM-mediated stress.…”
Section: Discussionsupporting
confidence: 80%
“…2 according to their rankings, including alcoholism as well as NF-κB and extracellular matrix (ECM)-receptor interaction signaling pathways. NOD-like receptor signaling was identified in VEC cell with HG stress, which was previously identified as a target pathway in HG-stressed fibroblast cells (12). These data indicated that HG regulates a large number of genes involved in different biological processes.…”
Section: Identification Of Hg-associated Transcriptome In Fibroblastsmentioning
confidence: 53%